2014
DOI: 10.1177/039463201402700309
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stem Cells Produce Bioactive Neurotrophic Factors: Source, Individual Variability and Differentiation Issues

Abstract: The first two authors contributed equally to this study This paper is dedicated to the memory of Gian Paolo Bagnara, master in mesenchymal stem cells, science, life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 39 publications
(40 reference statements)
1
21
0
1
Order By: Relevance
“…In our study, we found that the BDNF , CNTF , GDNF , and NTF3 genes were highly expressed in human PDLSCs, but not the IGF1 , NGF , VEGFA , FGF1 , FGF2 , TGFA , OCM , and LIF genes (Fig. A), indicating different spectra of neurotrophic factors secretion by human PDLSCs compared to MSCs from different tissue origins . Notably, we discovered a novel neuroprotective mechanism of human adult stem cells that retina coculture enhances BDNF secretion from human PDLSCs by more than twofold (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…In our study, we found that the BDNF , CNTF , GDNF , and NTF3 genes were highly expressed in human PDLSCs, but not the IGF1 , NGF , VEGFA , FGF1 , FGF2 , TGFA , OCM , and LIF genes (Fig. A), indicating different spectra of neurotrophic factors secretion by human PDLSCs compared to MSCs from different tissue origins . Notably, we discovered a novel neuroprotective mechanism of human adult stem cells that retina coculture enhances BDNF secretion from human PDLSCs by more than twofold (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…There is currently no therapy that sufficiently improves clinical recovery after ischemic stroke (Sims & Muyderman, ; Stankowski & Gupta, ). Adult neural stem cell (NSC) replacement therapy is a promising treatment for neurological recovery both structurally and functionally: It includes endogenous NSC regeneration to replace damaged tissue or neural cells in adulthood and exogenous adult NSC transplant after injuries such as ischemic stroke (Arvidsson, Collin, Kirik, Kokaia, & Lindvall, ; Chung et al, ; Koch, Kokaia, Lindvall, & Brustle, ; Paradisi et al, ). Adult NSCs are clinically important not only because ischemic stroke occurs mainly in adults but also because they are easy to obtain, with no medical ethics problems and no tumorigenicity (Giusto, Donega, Cossetti, & Pluchino, ).…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell based therapy is a new approach in neurodegenerative diseases on central nervous system (CNS) which is potent to solve major pathophysiologies due to the stem cells ability in reducing the inflammation, reconstructioning of blood brain barrier and making some neural regenerations by secreting some neurotrophic factors including basic fibroblast growth factor (bFGF), endothelial growth factor (EGF), brain derived neurotrophic factor (BDNF), vascular endothelial growth factor (VEGF), etc. ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%